Refusal of treatment among HER2-positive breast cancer patients in China: a retrospective analysis - Wang, Xin; Lian, Zhiwei; Wu, Qiyou; Wu, Fan; Zhang, Gong; Liu, Jian; Chen, Chuanben; Sun, Jing (Frontiers in Public Health, 2024)
Background: There is a need to update the understanding of treatment refusal among cancer patients in China, taking into account recent developments. This study investigated how public insurance coverage of the first breast cancer targeted therapy contributed to the changes in treatment refusal among HER2-positive breast cancer patients in China. And it intensively examined and discussed additional barriers affecting patient utilization of innovative anticancer medicines based on the types and reasons for treatment refusal.Methods: This retrospective study included female breast cancer patients diagnosed as HER2-positive who received treatment at a provincial oncology center in southern China between 2014 and 2020. Multivariate analysis was conducted using a binary logistic regression model. Subgroup analysis was performed with the same regression model.Results: Among the 1322 HER2-positive breast cancer patients who received treatment at the study hospital between 2014 and 2020, 327 (24.55%) had ever refused treatment. Economic reasons were reported as the primary cause by 142 patients (43.43%). Patients diagnosed before September 2017, when the first breast cancer targeted therapy was included in the public health insurance, were less likely to refuse treatment (OR=0.64, 95% CI:0.45 0.91, P=0.01) compared to those diagnosed after 2017. Patients enrolled in the resident health insurance were more likely to refuse treatment (OR=2.43, 95% CI:1.77 3.35, P<0.001) than those enrolled in the employee health insurance.Conclusions: This study reveals a high rate of treatment refusal among HER2-positive breast cancer patients, primarily attributed to financial factors. The disparity in public health insurance benefits resulted in a heavier economic burden for patients with less comprehensive benefits. Furthermore, the study identified challenges faced by patients seeking quality-assured cancer care in underdeveloped regions in China.